Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/1471-0528.17021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance of estimated fetal weight charts for the detection of small‐ and large‐for‐gestational age newborns with adverse outcomes: a French population‐based study

Abstract: Objective To compare the performance of estimated fetal weight (EFW) charts at the third trimester ultrasound for detecting small-and large-for-gestational age (SGA/LGA) newborns with adverse outcomes.Design Nationally representative observational study.Setting French maternity units in 2016.Population 9940 singleton live births with an ultrasound between 30 and 35 weeks of gestation. Methods We compared three prescriptive charts (INTERGROWTH-21st, World Health Organization (WHO), Eunice Kennedy Shriver Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 53 publications
(133 reference statements)
2
24
0
Order By: Relevance
“…Theoretically, such diagnoses could be used as inputs for improving obstetric and neonatal management in conjunction with other markers and pregnancy complications. However, as previous studies have shown 14,15,[23][24][25][26]36 and our study confirms, SGA or LGA diagnosis, when used in isolation without other predictors, performs poorly for predicting SNMM; in other words, the probability of SNMM (or neonatal death) is not materially changed by such a diagnosis. In our study, the expected risk of SNMM changed marginally from 20.2 per 1,000 live births to 23.8, 36.1 and 54.4 per 1,000 live births using a mild (10% increase in odds), moderate (50%) or extreme (100%) definition of SGA among female singletons at 39 weeks' gestation (Table 1).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Theoretically, such diagnoses could be used as inputs for improving obstetric and neonatal management in conjunction with other markers and pregnancy complications. However, as previous studies have shown 14,15,[23][24][25][26]36 and our study confirms, SGA or LGA diagnosis, when used in isolation without other predictors, performs poorly for predicting SNMM; in other words, the probability of SNMM (or neonatal death) is not materially changed by such a diagnosis. In our study, the expected risk of SNMM changed marginally from 20.2 per 1,000 live births to 23.8, 36.1 and 54.4 per 1,000 live births using a mild (10% increase in odds), moderate (50%) or extreme (100%) definition of SGA among female singletons at 39 weeks' gestation (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…The poor performance of SGA and LGA diagnoses in predicting SNMM and neonatal death weakens arguments regarding the superiority of references vs standards. 13,17,[19][20][21][22][23][24]37 For instance, diagnosis of SGA among term births using national references was associated with positive and negative likelihood ratios for perinatal death of 3.2 and 0.77, respectively; this changed the pretest probability of perinatal death to an inconsequential extent (from 1.7 per 1,000 total births to a posttest probability of 5.4 per 1,000 total births). 22 Similarly, the sensitivity, specificity, likelihood ratios and PAFs for neonatal morbidity associated with an SGA diagnosis based on customized charts was of limited utility at both the individual and population level (sensitivity and PAF for neonatal seizures 14.1% and 4.3%, respectively; sensitivity and PAF for glucose instability 22.9% and 14.0%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is common practice to use composite outcomes in FGR studies, one might argue that some of these outcomes can be a result of both the condition, i.e. placental insufficiency, and the treatment, which is often provider-initiated (relatively) premature or early term birth 7,8,14,[34][35][36] . We found that the group that experienced a decline in AC and/or EFW of > 50 percentiles had the lowest rate of spontaneous onset of labor and the highest rate of prelabor Cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Monier et al comparing the performance of different EFW references and standards for the prediction of small and large birth weight infants in France. 1 This is an exciting topic and the authors are to be commended for using a large national database to develop their arguments. We wish to make a number of comments on their analysis.…”
mentioning
confidence: 99%